2002
DOI: 10.1097/00006534-200201000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Combined Anterolateral Thigh Flap and Vascularized Fibula Osteoseptocutaneous Flap in Reconstruction of Extensive Composite Mandibular Defects

Abstract: Extensive composite defects of the oromandibular area are usually created after the surgical treatment of T3 and T4 cancers, requiring complex reconstructive plastic surgical procedures. The preferred treatment method for this type of defect is reconstruction with two free flaps. The use of the vascularized fibula osteoseptocutaneous flap for the bone and inner lining defect is well known and accepted. Among the flaps that can be used for the outer lining and soft-tissue reconstruction, the two most commonly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 28 publications
1
141
1
4
Order By: Relevance
“…Most authors quote a maximum width for a primary closure of the donor site of 8 cm to 10 cm (3,7,25,(35)(36)(37)39,42); however, wider defects have been closed, such as a reported 12 cm defect in a patient with a relatively large thigh circumference secondary to a high body mass index (3). A primarily closed donor site may result in a long scar, but it is usually more aesthetically pleasing than when closed with a skin graft, which is commonly done if a donor site defect is too wide to safely close without significant tension (32,39).…”
Section: Skin Graftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most authors quote a maximum width for a primary closure of the donor site of 8 cm to 10 cm (3,7,25,(35)(36)(37)39,42); however, wider defects have been closed, such as a reported 12 cm defect in a patient with a relatively large thigh circumference secondary to a high body mass index (3). A primarily closed donor site may result in a long scar, but it is usually more aesthetically pleasing than when closed with a skin graft, which is commonly done if a donor site defect is too wide to safely close without significant tension (32,39).…”
Section: Skin Graftsmentioning
confidence: 99%
“…A primarily closed donor site may result in a long scar, but it is usually more aesthetically pleasing than when closed with a skin graft, which is commonly done if a donor site defect is too wide to safely close without significant tension (32,39). This aesthetic issue may preclude the use of this flap in the female population, and this issue must thoroughly be discussed during informed consent (16).…”
Section: Skin Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimata et al [17] and Wei et al [18] considered that 2 to 3 cutaneous perforators can be found to run through the medial edge of vastus lateralis. From our experience and the work of others, at least 1 suitable cutaneous perforator could be always found [19]. The first perforator with the largest diameter can be always found to exit within a 5-cm-diameter circle centered at the midpoint of the line between the anterior superior iliac crest and the superolateral border of the patella.…”
Section: Discussionmentioning
confidence: 62%
“…Cada vez existen más aportaciones en la bibliografía donde se utilizan dos colgajos para solucionar el problema de las reconstrucciones oromandibulares complejas. 1,2,[5][6][7][8][9][10][11] La combinación de varios colgajos pretende suplir los defectos que puede tener una reconstrucción única en defectos complejos. Cada colgajo se selecciona independientemente por sus características que lo hacen ideal para cada tipo de defecto, óseo y de partes blandas con la finalidad de conseguir un resultado estético y funcional superior a la utilización de un solo colgajo.…”
Section: Introductionunclassified